Respuesta :

Solving the two given equation simultaneously to solve for x and y using the substitution method

[tex]\begin{gathered} y+2x=-1 \\ y=\frac{1}{2}x+4 \end{gathered}[/tex]

Since y is defined from the second equation, we substitute for y in the first equation to get

[tex]\begin{gathered} \frac{1}{2}x+4+2x=-1 \\ \text{collect like terms} \\ \frac{1}{2}x+2x=-1-4 \\ \frac{x+4x}{2}=-5 \\ \frac{5x}{2}=-5 \\ 5x=-2\times5 \\ 5x=-10 \\ x=-\frac{10}{5} \\ x=-2 \end{gathered}[/tex]

Hence, the value of x=-2

RELAXING NOICE
Relax